The Effect of Finish-Milling Operation on Surface Quality and Wear Resistance of Inconel 625 Produced by Selective Laser Melting Additive Manufacturing - KAYNAK, YUSUF (SPRINGER-VERLAG SINGAPORE PTE LTD, 2020)
Additive Manufacturing (AM) has been recognized as a promising manufacturing technology for the industries including aerospace and biomedical; however, the surface finish requirement for the components used in such industries imposes a severe constraint. Thus, finishing process for any manufacturing operation including additive manufacturing needs to be investigated to provide insights into the finish processing-surface property relationship. In this study, finishing operation in milling process is considered as a post-processing to improve the surface, mechanical and wear properties of the specimens fabricated by selective laser melting (SLM). This study demonstrates that surface and subsurface characteristic such as surface topography, surface roughness, microhardness, and wear resistance is substantially affected from milling parameters. Finish-milling operation with the high feed rate results in 50% reduction in wear rate of the specimen fabricated by SLM process.
Keywords: Additive manufacturing; Inconel 625; Surface quality; Wear resistance; Finish-milling